2019
DOI: 10.4236/mps.2019.93008
|View full text |Cite
|
Sign up to set email alerts
|

Four Cousins with Hypospadias, Is It Familial or Environmental? (Case Report)

Abstract: Hypospadias is one of the most common birth defects. However, its etiology remains largely unknown. Genetic and also intrauterine environmental factors have a principal role in causing familial hypospadias. Hypospadias repair is done through several techniques, one of which is Snodgrass technique which has many advantages. The 4 cousins underwent repair with no complications during 6 months follow up period. Methods: Urethroplasty using Snodgrass hypospadias repair of 4 cousins with positive parental consangui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Although we did not find a relationship between hypospadias and consanguinity ( p = .185), the marriage between close relatives has been associated with an increased risk of familial hypospadias. Several studies have reported cases of hypospadias in consanguineous families, suggesting a potential genetic influence on the condition (Frydman et al, 1985; Mohamed et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not find a relationship between hypospadias and consanguinity ( p = .185), the marriage between close relatives has been associated with an increased risk of familial hypospadias. Several studies have reported cases of hypospadias in consanguineous families, suggesting a potential genetic influence on the condition (Frydman et al, 1985; Mohamed et al, 2019).…”
Section: Discussionmentioning
confidence: 99%